2023
DOI: 10.1002/jmv.29018
|View full text |Cite
|
Sign up to set email alerts
|

Association of Remdesivir use with bradycardia: A systematic review and meta‐analysis

Abstract: Remdesivir has been used for coronavirus disease 2019 (COVID‐19) pneumonia with oxygen requirements that do not require mechanical intubation, and several studies showed a reduction in disease duration. However, there is a concern about bradycardia as its side effect. We aimed to investigate the association between Remdesivir and bradycardia by integrating findings from prior studies. We queried PubMed and EMBASE in February 2023 and performed a meta‐analysis of studies investigating bradycardia in patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Our study, previous case reports, and studies [42] have all emphasized the importance of evaluating patient characteristics associated with bradycardia during remdesivir treatment. Gaining insights into the risk factors associated with remdesivir-induced bradycardia is crucial for making informed decisions regarding patient management and treatment approaches.…”
Section: Discussionmentioning
confidence: 53%
“…Our study, previous case reports, and studies [42] have all emphasized the importance of evaluating patient characteristics associated with bradycardia during remdesivir treatment. Gaining insights into the risk factors associated with remdesivir-induced bradycardia is crucial for making informed decisions regarding patient management and treatment approaches.…”
Section: Discussionmentioning
confidence: 53%
“…Our results showed that the risk of bradycardia in the eGFR <30 cohort was comparable to that in the eGFR ≥30 cohort. Current reports have almost exclusively compared remdesivir users with non-users, and limited studies compared the same groups as our condition [ 51 , 52 ]. Furthermore, previous studies have been inconsistent regarding whether renal function may be a risk factor for bradycardia in remdesivir recipients; while Ai et al.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 1, the updated pooled incidence of bradycardia among COVID-19 patients receiving remdesivir treatment was 32.5% (95% CI: 21.7%-45.4%, I 2 = 98.8%). The total sample size was substantially larger than that of the original analysis, 1 and the confidence intervals were narrowed, indicating improved precision of the bradycardia incidence estimate associated with remdesivir. The risk of bias was assessed using the Newcastle-Ottawa Scale (NOS) or the Cochrane Risk of Bias 2.0 (ROB 2.0) tool, which revealed that six of the included studies were classified as having a low risk of bias (i.e., NOS ≥ 7 stars) (Figure 1).…”
Section: Dear Editormentioning
confidence: 92%
“…Although an association between remdesivir and bradycardia was established in the study by Ishisaka et al, 1 the wide confidence interval (i.e., 6.5%-54.4%) may indicate imprecision in the estimate of the pooled incidence. An accurate estimate of the incidence would better inform clinicians about the risks to discuss with patients and the appropriateness of cardiac monitoring.…”
Section: Dear Editormentioning
confidence: 93%
See 1 more Smart Citation